2009
DOI: 10.1007/s12325-009-0062-1
|View full text |Cite
|
Sign up to set email alerts
|

A combination povidone-iodine 0.4%/dexamethasone 0.1% ophthalmic suspension in the treatment of adenoviral conjunctivitis

Abstract: An ophthalmic suspension containing povidone-iodine 0.4% and dexamethasone 0.1% may be a useful agent in the treatment of acute RPS Adeno Detector-positive conjunctivitis. A further placebo-controlled study with a larger number of patients is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
3
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 15 publications
1
38
3
4
Order By: Relevance
“…However, a clinical trial carried out in children did not fi nd differences in the rate of healing between those treated with 1.25% povidone iodine or with antibiotic [75]. The use of topical antibiotics to prevent bacterial superinfection should be reserved for high-risk pediatric patients [73,75].…”
Section: Therapy Of Epidemic Keratoconjunctivitis (Ekc)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, a clinical trial carried out in children did not fi nd differences in the rate of healing between those treated with 1.25% povidone iodine or with antibiotic [75]. The use of topical antibiotics to prevent bacterial superinfection should be reserved for high-risk pediatric patients [73,75].…”
Section: Therapy Of Epidemic Keratoconjunctivitis (Ekc)mentioning
confidence: 99%
“…Topical cyclosporine A should only be considered in patients with subepithelial infi ltrates that produce significant visual acuity loss and do not respond to topical corticoid therapy [73,74]. One of the ophthalmic broad spectrum antiseptics is povidone-iodine.…”
Section: Therapy Of Epidemic Keratoconjunctivitis (Ekc)mentioning
confidence: 99%
“…35,36 A study by Pelletier et al investigated a topical combination agent that contained 0.4% povidone-iodine as an anti-viral and 0.1% dexamethasone as a potent steroid. 37 The expectation of the study was to ''effectively treat both the inflammatory and infectious components of acute adenoviral conjunctivitis by decreasing the symptomatic period following infection, shortening the duration of viral shedding and reducing the potential for infectious transmission.'' 37 The study followed the clinical course of positive RPS Adeno Detector conjunctivitis while monitoring serial virology markers by quantitative PCR and CC-IFA.…”
Section: Introductionmentioning
confidence: 99%
“…37 The expectation of the study was to ''effectively treat both the inflammatory and infectious components of acute adenoviral conjunctivitis by decreasing the symptomatic period following infection, shortening the duration of viral shedding and reducing the potential for infectious transmission.'' 37 The study followed the clinical course of positive RPS Adeno Detector conjunctivitis while monitoring serial virology markers by quantitative PCR and CC-IFA. 37 The results demonstrated that all eyes had rapid improvement of conjunctival injection and discharge with a decrease in viral titers at the same time, warranting a need for further study of this combination agent.…”
Section: Introductionmentioning
confidence: 99%
“…Successful use has been reported in human adenoviral conjunctivitis. 6 Although adenoviruses are often the cause of prolonged ocular morbidity and outbreaks of infectious conjunctivitis, other, more virulent, organisms may rapidly destroy ocular tissue. Some of these microbes are highly resistant bacteria with multiple virulence factors.…”
mentioning
confidence: 99%